Legitimidade ativa na ação de repetição do indébito tributário - Pria, Rodrigo Dalla (2016)
This present study aims to identify, from the joint interpretation and systematics of articles 165 and 166 of Brazilian Taxation Code (CTN) and article 18 of the Code of Civil Procedure (CPC), from the point of view of “assertion theory”, the legal criteria identification of legal standing to charge a claim for refund of undue payment